Os primórdios do esporte no sistema ONU: I MINEPS (1976) e Carta Internacional de Educaçao Física (1978) - Melo, Marcelo Paula de (2015)
In the sport field, Physical Education, which is a curricular discipline in basic education, and body practices of the UN education system started to have an active participation from the 1970s. The aim of this paper is precisely to analyze the documents and central events in the early days in the relationship between the UN system and its indications for political sports, Physical Education and body practices. Thus, we can understand the outlines of greater integration and organic nature of the actions in the Sport field and Physical Education, seeking to fulfill its role of a worldwide organic intelectual group